4‐month moxifloxacin containing regimens in the treatment of patients with sputum‐positive pulmonary tuberculosis in South India – a randomised clinical trial. Issue 4 (3rd February 2020) - Velayutham, Banurekha; Jawahar, Mohideen Shaheed; Nair, Dina; Navaneethapandian, Pooranagangadevi; Ponnuraja, Chinnaiyan; Chandrasekaran, Kandasamy; Narayan Sivaramakrishnan, Gomathi; Makesh Kumar, Marimuthu; Paul Kumaran, Paramasivam; Ramesh Kumar, Santhanakrishnan; Baskaran, Dhanaraj; Bella Devaleenal, Daniel; et al.
Abstract: Background: Shortening tuberculosis (TB) treatment duration is a research priority. We tested the efficacy and safety of 3‐ and 4‐month regimens containing moxifloxacin in a randomised clinical trial in pulmonary TB (PTB) patients in South India. Methods: New, sputum‐positive, adult, HIV‐negative, non‐diabetic PTB patients were randomised to 3‐ or 4‐month moxifloxacin regimens [moxifloxacin (M), isoniazid (H), rifampicin (R), pyrazinamide (Z) and ethambutol (E)] or to a control regimen (2H3 R3 Z3 E3 /4R3 H3 ) [C]. The 4 test regimens were 3R7 H7 Z7 E7 M7 [M3], 2R7 H7 Z7 E7 M7 /2R7 H7 M7 [M4], 2R7 H7 Z7 E7 M7 /2R3 H3 M3 [M4‐I] or 2R7 H7 Z7 E7 M7 /2R3 H3 E3 M3 [M4‐IE]. Treatment was directly observed. Clinical and bacteriological assessments were done monthly during treatment and for 24 months post‐treatment. The primary end point was TB recurrence post‐treatment. Results: Of 1371 patients, randomised, modified intention‐to‐treat (ITT) analysis was done in 1329 and per‐protocol (PP) analysis in 1223 patients. Regimen M3 was terminated due to high TB recurrence rates. 'Favourable' response at end of treatment was 96–100% in the moxifloxacin regimens and 93% in the control  regimen. Among these, the TB recurrence occurred in 4.1% in the M4 regimen and in 4.5% in the control regimen and demonstrated equivalence within a 5% margin (95% CI −3.68, 4.55). Similar findings were observed in modified ITT analysis. The TB recurrence rates in the M4‐I and M4‐IE regimens did not show equivalence with the control regimen. Sixteen (1.4%) of 1087 patients in the moxifloxacin regimens required treatment modification. Conclusion: The 4‐month daily moxifloxacin regimen [M4] was found to be equivalent and as safe as the 6‐month thrice‐weekly control regimen. Abstract : Contexte: La réduction de la durée du traitement de la tuberculose (TB) est une priorité de recherche. Nous avons testé l'efficacité et la sécurité de schémas thérapeutiques contenant de la moxifloxacine pendant 3 et 4 mois dans un essai clinique randomisé chez des patients atteints de TB pulmonaire (PTB) dans le sud de l'Inde. Méthodes: De nouveaux patients PTB, adultes, non diabétiques, positifs pour les expectorations, VIH négatifs ont été randomisés pour des schémas thérapeutiques contenant de la moxifloxacine pendant 3 mois ou 4 mois [moxifloxacine (M), isoniazide (H), rifampicine (R), pyrazinamide (Z), l'éthambutol (E)] ou pour un régime témoin (2H3 R3 Z3 E3 /4R3 H3 ) [C]. Les 4 régimes de l'essai étaient 3R7 H7 Z7 E7 M7 [M3], 2R7 H7 Z7 E7 M7 /2R7 H7 M7 [M4], 2R7 H7 Z7 E7 M7 /2R3 H3 M3 [M4‐I] ou 2R7 H7 Z7 E7 M7 /2R3 H3 E3 M3 [M4‐IE]. Le traitement a été directement observé. Les évaluations cliniques et bactériologiques ont été effectuées mensuellement au cours du traitement et durant 24 mois après le traitement. Le critère d'évaluation principal était la récidive de la TB après le traitement. Résultats: Des 1.371 patients randomisés, une analyse en intention de traiter (ITT) modifiée a été effectuée sur 1.329 et une analyse par protocole (PP) sur 1.223 patients. Le régime M3 a été interrompu en raison de taux élevés de récidive de la TB. La réponse «favorable» à la fin du traitement était de 96 à 100% dans les bras moxifloxacine et 93% dans le bras témoin. Parmi ceux‐ci, la récidive de la TB est survenue chez 4, 1% dans le schéma M4 et chez 4, 5% dans le schéma témoin et a démontré une équivalence dans une marge de 5% (IC95%: −3, 68, 4, 55). Des résultats similaires ont été observés dans l'analyse ITT modifiée. Les taux de récidive de la TB dans les schémas M4‐I et M4‐IE n'ont pas montré d'équivalence avec le schéma témoin. 16 (1, 4%) des 1.087 patients dans les régimes à moxifloxacine ont nécessité une modification du traitement. Conclusion: Le régime quotidien de moxifloxacine pendant 4 mois [M4] s'est avéré équivalent et aussi sûr que le régime témoin de trois fois par semaine pendant 6 mois.